Performance and recovery effects of Breathe Right nasal strips during a simulated hockey period - Deyak, J. A.; Goldsworthy, S.; Meierhofer, D; Bacharach, D. (Medicine & Science in Sports & Exercise, 1998)
Ice-hockey players (N = 8) were evaluated for skating speed and recovery while using Breathe Right nasal strips. Two simulated hockey periods separated by 15 minutes of rest required each S to perform two sets of six repeated shifts of 30-40 second skating bursts around a multi-directional course with 120 seconds of rest between each burst. Resting heart rate and rating of perceived exertion were measured at the end of each 150-second shift. During the second, fourth and sixth shift lactates were sampled. Blood lactates were lower for the skating bursts and the recovery periods when using the nasal strips. Skating performances were also better when wearing nasal strips. Implication. Hockey players might benefit from wearing nasal strips when playing hockey.